Improving Commitment among Employees with Human Resource Management Practices: Evidence from Insurance Companies (Patan Prospective Journal, 2024)
Developing a committed workforce is critical to the success of today's businesses. In this regard, this study aims to analyze the association of HRM practices on commitment among employees of Nepalese insurance companies. This study employs a descriptive research approach. 30 sets of questionnaires in each of the six insurance companies were distributed. The study reveals a positive and significant relationship between employee commitment and HRM practices in insurance companies. The results reveal that an effective and enhanced compensation plan is vital since it clarifies the staff's developing position and gives them a better long-term perspective. Organizing training and development events regularly for employees to improve their abilities, stimulate innovation, and improve performance is also critical for increasing employee commitment. Furthermore, companies should implement a successful system for performance reviews to assist employees in carrying out their obligations. Such practices ultimately help in improving employee commitment.